Muscle power and repeated sprint ability in soccer players - Saray Giovana dos Santos; Luiz Guilherme Antonacci Guglielmo; Juliano Fernandes da Silva; Daniele Detanico; Carlos Miguel Porto Almeida; Juliano Dal Pupo (Universidade Federal de Santa Catarina, 2010)
Muscle power is one of the most important physical qualities of soccer playerperformance and needs to be maintained during a match. Thus, the aim of this study was toinvestigate the levels of muscle power in soccer players before and after performing repeatedsprints (RS), and the association between power and RS performance. Twenty soccer playersfrom the under-20 category aged 18-20 years participated in this study. The study consisted ofthe execution of vertical jumps, execution of RS, new execution of vertical jumps, and collectionof blood samples. The continuous jump (CJ) test was performed on a piezoelectric force platformfor the measurement of muscle power and the RAST test was used to evaluate RS ability. Nosignificant difference in the levels of muscle power was observed after RS (p=0.57). Significantdifferences were observed in the first to fifth sprint times (p<0.01), but not between the fifth andsixth sprint (p=0.06). CJ height before RS was correlated with first sprint time (r=-0.62, p<0.01),best sprint time (r=-0.60, p<0.01), and average sprint time (r= -0.54, p<0.01). In conclusion,the soccer players studied showed no significant reduction in muscle power after RS. A decreasein performance was observed from the first to the fifth sprint, but not between the fifth and sixthsprint. The muscle power of soccer players was a determinant factor to perform one maximumsprint, as well as successive sprints.